Manajemen dan Pengawasan Proyek Rekonstruksi Jalan Geneng – Maron - Titan Adya Safara; Nur Ahmad Husin; Yudhi Arnandha; Budi Suswanto; Tatas Tatas (Pusat Riset dan Inovasi Nasional, 2025)
Construction work or construction projects are a collection of complex tasks interconnected with each other. In its implementation, these construction projects must be adjusted to the plans that have been made, both in terms of volume, quality, cost, and time. The execution of these projects requires management and supervision by a supervisory team, which acts as a consultancy service provider to assist the Public Works and Spatial Planning Agency of Temanggung Regency. This project is the Reconstruction Package of the Geneng – Maron Road Section located in Temanggung Regency. Temanggung Regency is a regency located in Central Java Province which serves as one of the connectors between the Capital of Central Java Province and other cities or regencies. Road maintenance is carried out periodically as one of the efforts to maintain district roads. Routine road maintenance is carried out once a year, but for the improvement of the Geneng – Maron road section, it is carried out after the last improvement in 2016. Based on the Minister of Public Works Regulation No. 13/PRT/M/2011 regarding Procedures for Road Maintenance and Road Inspection, there is a table determining the road maintenance program for asphalt/concrete-covered roads, indicating that roads in severe disrepair should undergo reconstruction or improvement. The Geneng – Maron road itself is a district road frequently traversed by various classes of vehicles. However, the Geneng – Maron Road should have its status changed due to frequent passage by heavy-duty vehicles, causing it to deteriorate more rapidly due to its design and function being inadequate. Therefore, routine maintenance cannot be applied this year because the damage is already severe enough to require road reconstruction.